Washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) and its fabrication process for lithium-sulfur batteries

The cleaned sulfur-impregnated 3D carbonized carbon nanofiber foam addresses the insulating and volume expansion issues in lithium-sulfur batteries, enhancing stability and capacity through a novel manufacturing process.

JP2025501004APending Publication Date: 2025-01-15COUNCIL OF SCI & IND RES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024539707
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2022-12-15
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face issues with insulating properties of sulfur, significant volume expansion, and polysulfide shuttling, leading to reduced capacity and cycling instability due to conventional carbon-based electrode materials.

Method used

A cleaned sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) is developed, manufactured through a method involving carbon nanofiber treatment, impregnation with sulfur, and washing to enhance stability and conductivity.

Benefits of technology

The solution provides high sulfur loading capacity and long cycle life for lithium-sulfur batteries by stabilizing the electrode and reducing polysulfide shuttling, resulting in improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501004000001
    Figure 2025501004000001
  • Figure 2025501004000002
    Figure 2025501004000002
  • Figure 2025501004000003
    Figure 2025501004000003
Patent Text Reader

Abstract

Washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) and its fabrication process for lithium-sulfur batteries The present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries and a method for its manufacture. The washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) functions as an electrode and exhibits high sulfur loading and stability, improving the energy storage capacity and lifespan of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the field of lithium-sulfur batteries. In particular, the present disclosure provides a washed sulfur-impregnated 3D carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries. The present disclosure also relates to a method for manufacturing the SCCNF-f-AW.

Background Art

[0002] The background description includes information that may be useful for understanding the present invention. It is not admitted that any of the information provided herein is prior art, relevant to the presently claimed invention, or that any of the publications specifically or implicitly referenced are prior art.

[0003] Lithium-sulfur (Li-S) batteries have a very high theoretical specific capacity of about 1675 mAh g -1 , an energy density of about 2600 Wh kg -1 , which is about 3 to 5 times that of commercially available conventional lithium-ion batteries. Therefore, they have emerged as promising next-generation energy storage systems. However, due to the insulating property of sulfur (5×10 -30 S cm -1 ) at 25°C, a large volume expansion (about 79%) during lithiation, and the shuttling of polysulfides [Li2S x (3 < x ≦ 8)], the cycle performance of the battery is significantly reduced, resulting in capacity degradation and cycle instability. This reduces the utilization rate of sulfur as the active material of the electrode and hinders the practical application of lithium-sulfur batteries.

[0004] The shuttle effect has been addressed in the art by applying several strategies, such as the use of various types of carbon materials, polar binding additives, and separator modifications (Fang R, Zhao S, Sun Z, Wang DW, Cheng HM, and Li F 2017, Adv. Mater. 29 1606823). In addition, various carbon-based materials (hosts) have been used as sulfur-impregnated positive electrodes in lithium-sulfur batteries or to capture polysulfide species in lithium-sulfur batteries. However, these carbon-based conductive materials in lithium-sulfur batteries suffer from certain drawbacks, such as electrode surface defects, limited energy density, and poor sulfur loading capacity and stability, which result in a short life cycle of lithium-sulfur batteries.

[0005] In view of the above shortcomings, there is a need in the art for a sulfur-impregnated carbon-based electrode material for lithium-sulfur batteries and a method for manufacturing the same that can overcome one or more shortcomings associated with conventional carbon-based electrode materials for lithium-sulfur batteries and methods for manufacturing the same. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Fang R, Zhao S, Sun Z, Wang DW, Cheng HM, and Li F 2017, Adv. Mater. 29 1606823 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present disclosure is to overcome one or more drawbacks associated with conventional carbon-based electrode materials and methods for making the same for lithium-sulfur batteries.

[0008] Another objective of the present disclosure is to provide washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries.

[0009] Another objective of the present disclosure is to provide washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) to function as a cathode in lithium-sulfur batteries.

[0010] Another objective of the present disclosure is to provide washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) that is stable and provides long life to lithium-sulfur batteries.

[0011] Another objective of the present disclosure is to provide a simple and economical method for fabricating washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries.

[0012] Yet another object of the present disclosure is to provide a lithium-sulfur cell comprising said sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) as a cathode. [Means for solving the problem]

[0013] The present disclosure relates to the field of lithium-sulfur batteries. In particular, the present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries. The present disclosure also relates to a method for producing said SCCNF-f-AW.

[0014] One aspect of the present disclosure is a 20m 2 g -1 ~25m 2 g -1 The present study relates to composites comprising washed sulfur-impregnated 3D carbonized carbon nanofiber foams (SCCNF-f-AW) with surface areas in the range of 1 nm and pore sizes in the range of 2 nm to 5 nm for lithium-sulfur batteries.

[0015] In one embodiment, the washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) has a molecular weight of 23 m. 2 g -1 and pore diameters in the range of 2 nm to 5 nm.

[0016] Another aspect of the present disclosure relates to a method for producing washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries, the method comprising the steps of: (i) taking carbon nanofiber powder (CNF) and refluxing it with HNO3 to obtain carbon nanofiber (CNF) powder; (ii) washing the carbon nanofiber (CNF) powder obtained in step (i) with deionized water and ethanol, and drying to obtain functionalized carbon nanofiber powder (f-CNF); (iii) dispersing the functionalized carbon nanofiber powder in deionized water in a ratio ranging from 4:1 to 6:1 and sonicating to disperse; (iv) adding glutaraldehyde, resorcinol, and sodium tetraborate decahydrate to the above obtained sonicated mixture of step (iii); (v) freezing and drying the mixture obtained in step (iv) to obtain 3D carbon nanofiber foam (CNF-f); (vi) heat treating the 3D carbon nanofiber foam (CNF-f) to obtain a 3D carbonized carbon nanofiber foam (CCNF-f); (vii) impregnating the 3D carbonized carbon nanofiber foam (CCNF-f) obtained in step (vi) with sulfur by heating the CCNF-f with elemental sulfur powder to obtain sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f); and (viii) washing the sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f) obtained in step (vii) with a solvent to remove excess sulfur to obtain washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW).

[0017] In one embodiment, in step (i), carbon nanofibers (CNF) are refluxed with HNO3 at a temperature ranging from 50°C to 70°C for a time period ranging from 4 hours to 10 hours. In one embodiment, in step (iii), carbon nanofiber powder (CNF) is dispersed in distilled water in a ratio of 5:1. In one embodiment, in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature ranging from 700°C to 900°C. In one embodiment, in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature ranging from 800°C. In one embodiment, the impregnation in step (vii) is carried out at a temperature ranging from 160°C to 220°C for a time period ranging from 1 hour to 3 hours. In one embodiment, the solvent is selected from any one or combination of toluene, chlorobenzene, toluene, p-xylene, and cyclohexane.

[0018] Yet another aspect of the present disclosure relates to a lithium-sulfur cell comprising: (i) A cathode containing washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW); (ii) an anode; (iii) a separator; and (iv) Electrolytes.

[0019] In one embodiment, the separator comprises a coating of functionalized multi-walled carbon nanotubes (f-MWCNTs).

[0020] In one embodiment, the washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) has a concentration of 1.2 mg cm -2 ~1.8mgcm -2 The sulfur loadings range from 0.01 to 0.1.

[0021] The accompanying drawings are included to provide a further understanding of the present disclosure, and are incorporated in and constitute a part of this specification. The drawings illustrate exemplary embodiments of the present disclosure, and together with the description, serve to explain the principles of the disclosure. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1(a) and FIG. 1(b) show exemplary snippets illustrating powder X-ray diffraction (p-XRD) patterns of 3D carbonized CNF foam (CCNF-f) and sulfur-impregnated 3D carbonized CNF foam (SCCNF-f-AW), respectively, according to an embodiment of the present disclosure. [Diagram 2] 2(a) and 2(b) show example snippets illustrating Raman spectra of CCNF-f and SCCNF-f-AW, respectively, according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 shows an example snippet illustrating the pore size distribution of CCNF-f) and SCCNF-f-AW using nonlocal density functional theory (NLDFT) in accordance with an embodiment of the present disclosure. [Figure 4] FIG. 4 shows an exemplary snippet illustrating the BET N2 adsorption-desorption isotherms of CCNF-f and SCCNF-f-AW in accordance with an embodiment of the present disclosure. [Diagram 5] 5(a) through 5(f) show example snippets illustrating survey spectra of CCNF-f and SCCNF-f-AW, according to an embodiment of the present disclosure. [Figure 6] 6(a) to 6(h) show exemplary snippets showing scanning electron micrographs of CCNF-f and SCCNF-f-AW according to embodiments of the present disclosure. [Figure 7] 7(a) and 7(b) show example snippets illustrating 3D volume-rendered X-ray tomography of CCNF-f and SCCNF-f-AW, respectively, according to an embodiment of the present disclosure. [Figure 8] FIG. 8(a) and FIG. 8(b) show example snippets illustrating pore size distributions obtained from tomography analysis of CNF-f and CCNF-f, respectively, according to embodiments of the present disclosure. [Figure 9]9(a) and 9(b) show example snippets illustrating segmented 3D X-ray tomography of CNF-f and CCNF-f, respectively, according to an embodiment of the present disclosure. [Figure 10] FIG. 10 shows an example snippet illustrating a 3D visualization of pores in CCNF-f in accordance with an embodiment of the present disclosure. [Figure 11] FIG. 11 shows exemplary snippets illustrating (a) cyclic voltammogram (CV) at a scan rate of 0.1 mV s-1, (b) electrochemical impedance spectra before and after CV measurement, (c) cycle stability at a current density of 100 mA g-1, and (d) specific capacity versus potential graph of sample SCCNF-f-AW according to an embodiment of the present disclosure. [Figure 12] FIG. 12 shows exemplary snippets illustrating (a) cyclic voltammogram (CV) at a scan rate of 0.05 mV s, (b) electrochemical impedance spectra before and after CV measurement, (c) cycle stability at a current density of 100 mA g, and (d) specific capacity versus potential plot of sample SCCNF-f-AW-CNT according to an embodiment of the present disclosure. [Figure 13] FIG. 13 shows a schematic diagram of a lithium-sulfur cell according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The following is a detailed description of the embodiments of the present disclosure, as illustrated in the accompanying drawings. The embodiments are described in detail to clearly communicate the disclosure. However, the amount of detail provided is not intended to limit the anticipated variations of the embodiments, but rather to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the present disclosure, as defined by the appended claims.

[0024] Each of the appended claims defines a separate invention and, for infringement purposes, shall be deemed to include the equivalent of the various elements or limitations set forth in the claim. Depending on the context, any reference below to the "invention" may refer to particular embodiments only. In other cases, any reference to the "invention" shall be deemed to refer to subject matter recited in one or more claims, but not necessarily to all claims.

[0025] The embodiments of the present specification and various features and advantageous details thereof will be more comprehensively described with reference to the non-limiting embodiments detailed in the following description. Descriptions of well-known components and processing techniques are omitted so as not to unnecessarily obscure the embodiments of the present specification. The examples used in the present specification are only intended to facilitate understanding of how to practice the embodiments of the present specification and to enable those skilled in the art to practice the embodiments of the present specification. Therefore, the examples should not be interpreted as limiting the scope of the embodiments of the present specification.

[0026] Unless otherwise specified, all terms used in disclosing the present invention, including technical and scientific terms, have the meaning commonly understood by one of ordinary skill in the art to which the present invention belongs. For further guidance, definitions of terms may be included to better understand the teachings of the present invention.

[0027] As used herein, the meanings of "a," "an," and "the" include the plurals unless the context clearly dictates otherwise. Also, as used herein, the meaning of "in" includes "in" and "on," unless the context clearly dictates otherwise.

[0028] As used herein, the terms "comprise, comprise, comprising," "include, includes, including" are intended to be open-ended, i.e., other steps or other ingredients can be added that do not affect the end result. The above terms encompass the terms "consisting of" and "consisting essentially of."

[0029] In some embodiments, the numerical parameters set forth in the specification are approximations and can vary depending upon the desired properties / conditions sought to be obtained by a particular embodiment. In some embodiments, the numerical parameters should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques. Notwithstanding that the numerical ranges and parameters setting forth the broad scope of some embodiments of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible.

[0030] The recitation of ranges of values ​​herein is intended to be merely a shorthand method of referring individually to each value falling within the range, and unless otherwise indicated herein, each individual value is incorporated into the specification as if it were individually set forth herein.

[0031] The headings and summaries provided herein are for convenience only and do not interpret the scope or meaning of the embodiments.

[0032] The present disclosure relates to the field of lithium-sulfur batteries. In particular, the present disclosure provides a washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries. The present disclosure also relates to a method for producing said SCCNF-f-AW. The lithium-sulfur battery produced using said SCCNF-f-AW exhibits high sulfur loading capacity, stability, and long life cycle.

[0033] One aspect of the present disclosure relates to a composite including washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries, having a surface area of ​​20 m 2 g -1 ~25m 2 g -1 In one embodiment, the washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) has a surface area of ​​23 m 2 g -1 and the pore diameter is in the range of 2 nm to 5 nm.

[0034] In an optional embodiment, the composite comprises a 3D carbonized carbon nanofiber foam (CNF) for lithium-sulfur batteries and has a surface area of ​​280 m 2 g -1 ~350m 2 g -1 Preferably, the 3D carbonized carbon nanofiber foam (CCNF-f) has a surface area of ​​310 m 2 g -1 and the pore size is less than 7 μm. More preferably, the composite has a pore size in the range of 2 nm to 7 μm, or a pore size in the range of 14 nm to 7 μm, and even more preferably a pore size in the range of small pores of 2 nm to 14 nm to large pores of 1 to 7 μm (CCNF has bimodal porosity, i.e., micropores in the range of 2-14 nm and micropores in the range of 1-7 μm).

[0035] One aspect of the present disclosure relates to a method for preparing washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries, the method comprising the steps of: (i) taking carbon nanofibers (CNF) and refluxing it with HNO3 to obtain carbon nanofiber (CNF) powder; (ii) washing the carbon nanofiber (CNF) powder obtained in step (i) with ethanol and drying to obtain carbon nanofiber foam (CNF-f); (iii) dispersing the carbon nanofiber foam (CNF-f) in deionized water in a ratio ranging from 4:1 to 6:1 and sonicating to disperse; (iv) adding glutaraldehyde, resorcinol, and sodium tetraborate decahydrate to the sonicated mixture obtained in above step (iii). (v) freezing and drying the mixture obtained in step (iv) to obtain 3D carbon nanofiber foam (CNF-f); (vi) heat treating the 3D carbon nanofiber foam (CNF-f) to obtain 3D carbonized carbon nanofiber foam (CCNF-f); (vii) impregnating the 3D carbonized carbon nanofiber foam (CCNF-f) obtained in step (vi) with sulfur by heating the CCNF-f with elemental sulfur powder to obtain sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f); and (viii) washing the sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f) obtained in step (vii) with a solvent to remove excess sulfur to obtain washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW).

[0036] In one embodiment, carbon nanofibers (CNFs) are refluxed in HNO3 at a temperature of 50°C to 70°C for 4 hours to 10 hours in step (i). In one embodiment, the refluxed carbon nanofiber (CNF) powder is first washed with distilled water until the pH is neutral before washing with ethanol. In one embodiment, the carbon nanofiber (CNF) powder obtained in step (i) is washed with water and ethanol. The use of carbon nanofibers as a starting material has the advantage that functionalization can be performed even at low temperatures (50°C to 70°C) when refluxing with HNO3.

[0037] In one embodiment, in step (iii), carbon nanofiber foam (CNF-f) is dispersed in deionized water in a ratio of 5: 1. In one embodiment, in step (iv), glutaraldehyde, resorcinol, and sodium tetraborate decahydrate are added, respectively, followed by ultrasonication of the dispersion.

[0038] In one embodiment, the mixture obtained in step (iv) is dried by any conventional method recognized by one of skill in the art to serve its intended purpose, hi one embodiment, drying is performed by vacuum drying.

[0039] In one embodiment, in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature of 700°C to 900°C. In one embodiment, in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature of 800°C. In one embodiment, the heat treatment is performed under an inert atmosphere. The heat treatment converts the 3D carbon nanofiber foam (CNF-f) with a cross-linked gel-like structure into a 3D carbonized carbon nanofiber foam (CCNF-f) with a conductive framework without compromising its structure. This improves the electrical conductivity and the performance of lithium-sulfur batteries. Heat treatment of the 3D carbon nanofiber foam (CNF-f) below the above temperature range results in the retention of the cross-linked gel-like structure, while heating above the above temperature range leads to the collapse of the foam structure.

[0040] In one embodiment, the impregnation in step (vii) is carried out at a temperature of 160° C. to 250° C. for 1 hour to 3 hours. In one embodiment, the impregnation in step (vii) is carried out at a temperature of 160° C. to 250° C. for 2 hours under inert atmosphere and then cooled to obtain sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f). In one embodiment, the impregnation in step (vii) is carried out at a temperature of 220° C. In one embodiment, the impregnation in step (vii) is carried out for 2 hours. In one embodiment, the solvent is selected from any one or combination of toluene, chlorobenzene, toluene, p-xylene, and cyclohexane. Washing the sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF) with a suitable solvent (which has an affinity for sulfur and is inert to carbon nanofiber foam) removes excess sulfur from the sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF) (reducing the dissolution of excess sulfur and preventing the formation of an insulating layer on the cathode) and results in washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW). The lithium-sulfur battery fabricated using the washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) is more stable and exhibits a longer life.

[0041] In one embodiment, after the sulfur impregnation and washing steps in the method disclosed herein, when SCCNF-f-AW is formed, the surface area and pore size of CCNFs are dramatically changed / reduced. That is, CCNFs have a surface area of ​​280 m 2 g -1 ~350m 2 g -1 range, with pore sizes less than 7 μm (bimodal pore size) and, after sulfur impregnation and washing, a surface area of ​​20 m 2 g -1 ~25m 2 g -1 and SCCNF-f-AW with pore diameters in the range of 2 nm to 5 nm can be obtained.

[0042] In one embodiment, the sulfur impregnation of CCNF-f achieves a very high sulfur content of about 50-95%. Preferably, the sulfur impregnation of CCNF-f achieves a sulfur content of 60-95%, 70-95%, 80-95%, or 95%.

[0043] Yet another embodiment of the present disclosure relates to a lithium-sulfur cell that includes: (i) a cathode comprising washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW); (ii) an anode; (iii) a separator; and (iv) an electrolyte.

[0044] In one embodiment, the washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) can achieve a yield of 1.2 mg cm in a lithium-sulfur cell. -2 to 1.8 mg cm -2 In one embodiment, it represents a sulfur loading in the range of 1.5 mg cm in a lithium sulfur cell. -2 In one embodiment, the separator comprises a coating of functionalized multi-walled carbon nanotubes (f-MWCNTs).

[0045] In one embodiment, the cathode comprises washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW), carbon black (Super P) and polyvinylidene difluoride (PVDF) in a ratio of 80:10:10 coated on a carbon coated aluminum foil.

[0046] In one embodiment, the anode is lithium metal. In one embodiment, the anode is lithium metal in the form of a disk.

[0047] In one embodiment, the separator comprises functionalized multi-walled carbon nanotubes (f-MWCNTs). In one embodiment, the (f-MWCNT) based separator aids in battery capacity retention due to polysulfide bonding with the functional groups on the MWCNTs. In one embodiment, the separator is Celgard 2325, which comprises a polypropylene-polyethylene-polypropylene (PP / PE / PP) tri-layer membrane as a lithium battery separator with a thickness of 20-30 microns. In one embodiment, the thickness is about 25 microns.

[0048] In one embodiment, the electrolyte comprises 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a 1:1 v / v mixture of 1,3-dioxolane and 1,2-dimethoxyethane, with 0.4 M LiNO3 as an additive.

[0049] In one embodiment, the lithium-sulfur cell comprises: (i) a cathode comprising washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW), carbon black (Super P) and polyvinylidene difluoride (PVDF) in a ratio of 80:10:10 coated on a carbon-coated aluminum foil; (ii) an anode comprising a lithium metal disk; (iii) a separator comprising a PP / PE / PP tri-layer membrane with a thickness in the range of 20-30 microns; and (iv) an electrolyte comprising 1 M LiTFSI in a 1:1 v / v mixture of 1,3-dioxolane and 1,2-dimethoxyethane with 0.4 M LiNO3 as an additive.

[0050] In one embodiment, the lithium-sulfur cell comprises: (i) a cathode comprising washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW), carbon black (Super P) and polyvinylidene difluoride (PVDF) in a ratio of 80:10:10 coated on a carbon-coated aluminum foil; (ii) an anode comprising a lithium metal disk; (iii) a separator comprising a PP / PE / PP tri-layer membrane coated with a slurry of functionalized multi-walled carbon nanotubes (f-MWCNTs) and PVDF binder (9:1 ratio) in N-methyl-2-pyrrolidone (NMP); and (iv) an electrolyte comprising 1 M LiTFSI in a 1:1 v / v mixture of 1,3-dioxolane and 1,2-dimethoxyethane with 0.4 M LiNO3 as an additive.

[0051] In one embodiment, multi-walled carbon nanotubes (MWCNTs) are functionalized by a process comprising the steps of: (i) refluxing the MWCNTs in 3M HNO3 in an oil bath, cooling to room temperature, followed by washing with distilled water to neutral pH, (ii) washing the powder from step (i) with absolute ethanol and drying. In one embodiment, a lithium-sulfur cell with washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) and functionalized multi-walled carbon nanotubes (f-MWCNTs) was designed to operate at 100 mAg -1 Approximately 845mAhg -1 and exhibits remarkable capacity retention in the lithium-sulfur cell (SCCNF-f-AW-CNT).

[0052] Although the subject matter has been described with reference to specific embodiments, this description should not be construed in a limiting sense. Various modifications of the disclosed embodiments, as well as alternative embodiments of the subject matter, will become apparent to those skilled in the art upon reference to the description of the subject matter. It is therefore contemplated that such modifications may be made without departing from the spirit or scope of the subject matter as defined.

[0053] example material Carbon nanofibers (SKU: 719803-25G), resorcinol, glutaraldehyde, sodium tetraborate decahydrate, 1,2-dimethoxyethane (DME), 1,3-dioxolane (DOL), LiNO3, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), N-methyl-2-pyrrolidone, polyvinylidene difluoride (PVDF) were procured from Sigma Aldrich and used without modification or further purification. Carbon black, Super P were procured from Alfa Aesar. Toluene (sulfur free) and HNO3 were procured from Thomas Baker Chemicals Pvt. Ltd. and used as received. Coin cell (CR-2032) components were procured from Global Nanotech. 10-walled MWCNTs were procured from Chemapol industries, Bombay, India.

[0054] Example 1 Synthesis of washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) Washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) was synthesized by the following steps.

[0055] 1. Preparation of carbon nanofiber foam (CNF-f) The carbon nanofibers were refluxed in 3M HNO3 at 60 °C for 6 h, followed by washing with copious amounts of deionized (DI) water until the pH was neutral. Then, the powder was washed with absolute ethanol and dried in an oven at 80 °C for 12 h (the dried product is hereafter referred to as "f-CNF"). f-CNF and distilled water were taken in a w / v ratio of 5:1 and sonicated to completely disperse. About 10 μL of glutaraldehyde was added to the dispersion and sonicated for about 15 min, after which 30 mg of resorcinol was added and sonicated again for about 15 min. Finally, 30 mg of sodium tetraborate decahydrate was added to the above solution and sonicated for about 15 min. The resulting dispersion was frozen using liquid nitrogen and vacuum dried (0.120 mbar) at -80 °C to obtain 3D carbon nanofiber foam (CNF-f).

[0056] 2. Heat treatment of 3D carbon nanofiber foam (CNF-f) to obtain 3D carbonized CNF foam (CCNF-f) The 3D carbon nanofiber foam (CNF-f) produced above was heat treated at 800 °C in an inert (argon gas) atmosphere for 2 h with a heating rate of 5 °C per minute to convert the crosslinked gel foam into a conductive carbon framework without compromising its structure. This was found to be advantageous for improving the performance of lithium-sulfur batteries due to enhanced electronic conductivity. The heat-treated foam samples were collected and labeled as "CCNF-f" (3D carbonized CNF foam).

[0057] 3. Impregnating CCNF-f with sulfur to obtain sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f) and washed sulfur-impregnated 3D carbonized carbon nanofiber (SCCNF-f-AW) Sulfur impregnation was performed by placing the CCNF-f in an alumina boat and completely covering the CCNF-f with fine elemental sulfur powder. The alumina boat was placed in a tubular furnace and heated to 350 °C at a heating rate of 5 °C per minute for 2 h under a continuous flow of argon gas. The set temperature in the furnace was 350 °C, while the measured temperature in the tubular furnace was about 220 °C. Samples were collected after the furnace reached room temperature and were called sulfur-impregnated 3D carbonized carbon nanofiber foams (SCCNF-f).

[0058] During the experiment, it was found that there was excess sulfur on the surface of SCCNF-f. Therefore, SCCNF-f was washed with toluene to remove excess sulfur and dried in a vacuum oven at 55 °C for 12 h. The final product was a washed sulfur-impregnated 3D carbonized carbon nanofiber foam, labeled as "SCCNF-f-AW." AW stands for "after wash," so named because the sample was washed after sulfur impregnation.

[0059] Example 2 Synthesis of sulfur-impregnated 3D carbonized CNF foams modified with functionalized multi-walled carbon nanotubes (SCCNF-f-AW-CNT) A coin cell (battery cell) was fabricated using a separator coated with sulfur-impregnated 3D carbonized CNF foam (SCCNF-f) modified with functionalized multi-walled carbon nanotubes (SCCNF-f-AW-CNT).

[0060] 1. Functionalization of multi-walled carbon nanotubes For functionalization, the multiwalled carbon nanotubes were refluxed in 3M HNO3 in an oil bath at 60 °C for 6 h. After cooling to room temperature, they were washed with distilled water until the pH reached neutral. The powder was then washed with absolute ethanol and dried in an oven at 80 °C for 12 h. SCCNF-f-AW-CNTs were prepared using the procedure described in Example 1.

[0061] 2. Characterization Powder X-ray diffraction patterns were recorded on a Phillips PANalytical diffractometer. Raman spectra were performed on a HR800 Raman spectrometer (Jobin-Yvon, Horiba, France) using a 632.8 nm red laser. X-ray photoelectron spectroscopy (XPS) measurements were performed on a VG Micro-Tech ESCA 3000 instrument. Nitrogen adsorption-desorption isotherm measurements were performed on a Quantachrome surface area analyzer; the specific surface area and pore size distribution of the samples were obtained by the Brunauer-Emmett-Teller (BET) model and nonlocal density functional theory (NLDFT). Thermogravimetric analysis was performed using an SDT Q600 DSC-TGA thermogravimetric (TGA) instrument.

[0062] 3D X-ray microtomographic imaging (Xradia 510 Versa X-ray microscope, Zeiss X-ray microscope, Pleasanton, CA, USA) was performed to investigate the morphology, porosity, and pore size distribution of the carbon nanofiber foams. The sample was mounted on a sample holder and placed between the X-ray source and the detector assembly. The detector assembly consisted of a scintillator, 20X optics, and a CCD camera. The X-ray source was ramped up to 80 kV and 7 W. Tomographic image acquisition was performed on a sample of 0.7x0.7x0.7 mm2 in size. 3The image was completed by acquiring 7001 projections with a 360° rotation with a pixel size of 0.68 microns for 1000 x 1000 x 1000 mm. In addition, projections without the sample in the beam (reference images) were also collected and averaged. The projections were reconstructed by a filtered back projection algorithm to generate two-dimensional (2D) virtual cross sections of the sample. Image denoising, filtering, segmentation and further processing were performed using the GeoDict software package (GeoDict®, 2018, Math2Market GmBH, Germany). The 2D virtual cross sections were further cropped to sub-volumes (100x100x100 voxels, 0.68 cubic microns per voxel), filtered to remove noise and segmented after OTSU threshold selection based on local minima from the grayscale histogram. The resulting 3D reconstructed models were used to estimate pore properties such as porosity, pore size distribution, etc. using the PoroDict® software package (GeoDict® 2018, Math2Market GmBH, Germany), where the pore radius was determined by fitting a sphere to the pore volume.

[0063] Figure 1(a) and Figure 1(b) show exemplary snippets showing the powder X-ray diffraction (p-XRD) patterns of 3D carbonized CNF foam (CCNF-f) and sulfur-impregnated 3D carbonized CNF foam (SCCNF-f-AW). Figure 1(a) shows a typical p-XRD spectrum of CCNF-f, with peaks of (002) and (100) planes appearing at 24.2° and 43°, respectively, corresponding to the partial graphitic character of the sample. This broadening is attributed to the amorphous carbonization of resorcinol-glutaraldehyde bonds by bridging carbon. After impregnation and subsequent washing, p-XRD confirmed the successful impregnation of the foam with sulfur. As shown in Figure 1(b), the diffraction peaks corresponding to sulfur in SCCNF-f-AW are in good agreement with the JCPDS card (#08-0247) for elemental sulfur. In the case of SCCNF-f-AW, the intensity of X-rays from sulfur is higher than that of carbon, and the diffraction peaks are dominant, so the peaks corresponding to CCNF-f could not be observed.

[0064] Figures 2(a) and 2(b) show the strength and I d / I g Exemplary snippets of Raman spectra of CCNF-f and SCCNF-f-AW, showing the change in the ratio, are shown in Figure 2(a). As shown in Figure 2(a), CCNF-f consists of two major peaks corresponding to the D and G bands, with a slightly higher intensity of the D band. The higher intensity of the D band indicates a higher defect density in CCNF-f after carbonization. Figure 2(b) shows the Raman spectrum of SCCNF-f-AW, which shows peaks at 153, 217.6, 433.3, and 471 cm, corresponding to the presence of sulfur, in addition to the D and G bands of the host material. -1 The figure shows several high intensity peaks centered around

[0065] The presence of high intensity peaks in p-XRD and Raman characterization confirmed successful impregnation of sulfur into the host carbon foam.

[0066] Figure 3 shows an exemplary snippet showing the pore size distribution of CCNF-f and SCCNF-f-AW using nonlocal density functional theory (NLDFT). To understand the porous properties of the fabricated foam materials, BET analysis was performed. The BET results were converted into pore size distribution (PSD) curves shown in Figure 3 using the NLDFT slit pore model to analyze the porosity distribution. The high volumetric adsorption of CCNF-f with pore diameters less than 2 nm indicates the significant presence of micropores. The presence of mesopores ranging from 2–5 nm to 8–14 nm in diameter is also observed in CCNF-f. However, SCCNF-f-AW shows a slightly lesser presence of mesopores with diameters ranging from 2–5 nm.

[0067] Figure 4 shows an exemplary snippet showing the BET N2 adsorption-desorption isotherms of CCNF-f and SCCNF-f-AW. CCNF-f showed the presence of type I and type IV BET isotherms with a significant amount of microporosity and substantial presence of mesopores. However, SCCNF-f-AW consisted of only type IV isotherms, indicating the presence of mesopores only, complementing the PSD results. The surface areas of CCNF-f and SCCNF-f-AW were estimated using MPBET technique and were found to be 310 and 23 m, respectively. 2 g -1 It turned out to be.

[0068] The results suggest that sulfur impregnation could block the surface pores of SCCNF-f-AW for N2 adsorption and significantly reduce the surface area.

[0069] X-ray photoelectron spectroscopy (XPS) analysis was carried out to analyze the elemental composition and bonding characteristics of the surfaces of CCNF-f and SCCNF-f-AW. The obtained spectra are shown in Figure 5(a) to Figure 5(f).

[0070] Figure 5(a) shows the survey spectra of CCNF-f and SCCNF-f-AW, confirming the presence of element S in the SCCNF-f-AW sample. Figure 5(b) and Figure 5(d) show the high-resolution spectra of C1s for CCNF-f and SCCNF-f-AW samples, respectively. The XPS spectra indicate the presence of CC and C=C, C-O, C=O, and O-C=O bonds in CCNF-f. In SCCNF-f-AW, a similar configuration was observed, except for a significant increase in the peak area around 285.7 eV assigned to C-O and C-S bonds. The increase in the peak area indicates the formation of C-S bonds, which also have a BE closer to the C-O bond, making them difficult to resolve individually.

[0071] Figure 5(c) and Figure 5(e) show the high-resolution spectra of O1s of CCNF-f and SCCNF-f-AW, respectively. Both materials show the predominant presence of C=O, CO, and OC=O bonds. In addition, the high-resolution O1s spectrum of SCCNF-f-AW further shows the presence of S-O bonds with binding energy in the range of 532.2 eV, which is the same as that of C=O. S=O appears with binding energy in the range of 533.2 eV, which is also the same range as that of CO bonds. The binding energy of 534.89 eV corresponds to the presence of OC=O bonds. The high-resolution spectrum of sulfur 2p peak of SCCNF-f-AW is shown in Figure 5(f). With peak split of 1.13 eV, both sulfur 2p peaks 2p1 / 2 and 2p3 / 2 indicate the significant presence of sulfur in SCCNF-f-AW.

[0072] Figure 6(a) shows an exemplary snippet showing scanning electron micrographs of CCNF-f and SCCNF-f-AW. Figure 6(a) and Figure 6(b) show that CCNF-f is composed of a 3D interconnected structure of carbon nanofibers formed by polymerization between f-CNFs using resorcinol and glutaraldehyde crosslinkers. Figure 6(c) and Figure 6(d) show the FESEM images of SCCNF-f-AW after impregnating CCNF-f with sulfur and washing with toluene. SEM images confirmed that the pores of CCNF-f are filled with impregnated sulfur while retaining the 3D network. Elemental mapping of SCCNF-f-AW is shown in Figure 6(e) to Figure 6(h). Figure 6(e) shows the SEM image and overlay image, while Figure 6(f) shows the presence of carbon and sulfur in the sample. Figure 6(g) and Figure 6(h) show the distribution of carbon and sulfur in the 3D foam. As evident from elemental mapping, the pores of CCNF-f are filled with impregnated sulfur.

[0073] Figure 7(a) and Figure 7(b) show exemplary snippets showing 3D volume-rendered X-ray tomography of CCNF-f and SCCNF-f-AW. Figure 7A shows the 3D pore arrangement of CCNF-f that retains its interconnected stacking even after carbonization at 800 °C. The structure of CCNF-f also shows the enhanced porosity of the foam after carbonization. The porosity of the fabricated CNF-f was found to be 70%, which further increased to 80% for CCNF-f due to the shrinkage of the interconnected carbon network as a result of heat treatment. Figure 7(b) shows the volume-rendered tomography image of SCCNF-f-AW to map the presence of S impregnated in the host. Extremely high sulfur loading could be observed without disturbing the CCNF-f structure after impregnation.

[0074] Figure 8(a) and Figure 8(b) show exemplary snippets showing the pore size distribution obtained from the tomography analysis of CNF-f and CCNF-f. The pore size distribution observed in the microtomography analysis was in micrometer size since the true spatial resolution limit of the instrument was 1 μm. As shown in Figure 8(a), the average pore size of the pores in CNF-f was about 4 μm, which further increased to about 7 μm in the case of CCNF-f after heat treatment (as shown in Figure 8(b)).

[0075] 9(a) and 9(b) show example snippets showing segmented 3D X-ray tomography of CNF-f and CCNF-f, respectively.

[0076] FIG. 10 shows an example snippet showing the 3D visualization of CCNF-f pores.

[0077] The BET results of CCNF-f show a collective porosity distribution in the micro-mesoporous range (nano domain). At the same time, the computer tomography estimation shows a porosity distribution in the micro domain with pores of 7 microns contributing to the maximum volume fraction of CCNF-f. The results show that CCNF-f foam has a bimodal porosity distribution in the micro and nano domains, making it an ideal host candidate for high sulfur loading as observed by TGA analysis.

[0078] Figure 11 shows the (a) 0.1 mV s -1 (b) cyclic voltammograms (CV) at a scan rate of 100 mAg; (c) electrochemical impedance spectra before and after CV measurements; -1 and (d) an exemplary snippet showing the specific capacity vs. potential graph. The SCCNF-f-AW coin cells were assembled with a composition of SCCNF-f-AW:PVDF:conductive carbon of 80:10:10.

[0079] Figure 11(a) shows the results at a scan rate of 0.1 mVs -1Figure 1 shows cyclic voltammograms recorded at 1000 K for 10 min at 2000 K. The cyclic voltammograms show characteristic peaks corresponding to typical Li-S electrochemical behavior with reversible reduction and oxidation processes. The reduction process occurs in two steps, with the first peak occurring at high potentials when S8 is converted to long-chain polysulfides (Li2S n、 4≦n≦8), and the long-chain polysulfides are further reduced to short-chain polysulfides (Li2S n A peak at approximately 2.0 V appeared due to the reduction of the polysulfides to S8 (1≦n<4). An oxidation peak associated with the reversible formation of short-chain polysulfides to long-chain polysulfides to S8 was observed at 2.46 V. Except for the first cycle, the subsequent cycles were overlapping, indicating excellent electrochemical reversibility.

[0080] Figure 11(b) shows the impedance spectroscopy measurements before and after CV. The series resistance of the cell was 3.2 Ω and the charge transfer resistance was 231 Ω, but after CV the series resistance was about 5.4 Ω and the charge transfer resistance was about 18.8 Ω.

[0081] Figure 11(c) shows the current density of 100 mAg -1 The cycle data shows that the initial discharge capacity is about 694mAhg -1 After 50 cycles, it was 228mAhg -1 It decreased to.

[0082] Figure 11(d) shows a plot of specific capacity versus potential, which shows two distinct charge-discharge plateaus associated with redox reactions between Li and S, which were found to be characteristic of lithium-sulfur batteries. These plateaus are in good agreement with the redox peaks appearing in the CV curves. The formation of soluble long-chain lithium polysulfides was noted by the appearance of a discharge plateau at higher potentials. The discharge plateau at lower potentials is due to the reduction of long-chain polysulfides to short-chain polysulfides.

[0083] Figure 12(a) to (d) show the (a) 0.05 mVs -1(b) cyclic voltammograms (CV) at a scan rate of 100 mAg; (c) electrochemical impedance spectra before and after CV measurements; -1 and (d) exemplary snippets showing the rate capacity data. The fabrication followed the following procedure.

[0084] Modification of separators in coin cells with MWCNTs Modifying the separator with MWCNTs helps in capacity retention because polysulfides bind with the functional groups on the MWCNTs. In this invention, the separator was further modified with functionalized multi-walled carbon nanotubes (f-MWCNTs) to improve capacity retention and reduce polysulfide dissolution.

[0085] 3. Preparation of Functionalized Multiwalled Carbon Nanotubes For functionalization, the multiwalled carbon nanotubes were refluxed in 3M HNO3 in an oil bath at 60 °C for 6 h. After cooling to room temperature, they were washed with deionized water until the pH reached neutral. The powder was then washed with absolute ethanol and dried in an oven at 80 °C for 12 h.

[0086] Electrochemical studies of lithium-sulfur coin cells with modified separators The f-MWCNTs were coated onto the separator by making a slurry of f-MWCNTs and PVDF binder (9:1) in NMP. The cells were fabricated such that the f-MWCNT-coated side of the separator faced the cathode. The electrochemical results using the modified separator are shown in Figure 12(a) to Figure 12(d).

[0087] Figure 12(a) shows the results at a scan rate of 0.05 mVs -1 The CV performed at 2.25 V showed two clear reduction peaks, the first of which was the long-chain polysulfide Li2S n (4≦n≦8), and the second peak at about 2.0 V corresponds to the further reduction of the long-chain polysulfides to short-chain Li2S2 / Li2S. The oxidation peak at 2.5 V is due to the formation of long-chain polysulfides from the short-chain polysulfides and then the formation of S8.

[0088] Figure 12(b) shows the impedance spectra before and after the CV measurements. The series resistance of the cell was about 3.6 Ω and increased to 15.8 Ω after 5 cycles. The charge transfer resistance before CV was about 81 Ω and increased to about 206 Ω after cycling. A decrease in the charge transfer resistance of the cell using the MWCNT separator was observed. This increase in series resistance and charge transfer resistance after cycling was due to the trapping of polysulfides by the MWCNT coating on the separator.

[0089] Figure 12(c) shows the current density of 100 mAg -1 The first and second cycles are shown at a current density of 10 mA / s. -1 and 25mAg -1 Cycled at 100mAg for subsequent cycles -1 The initial discharge capacity was about 845mAhg. -1 After 46 cycles, it was about 567mAhg -1 The capacity retention rate was significantly improved by improving the separator.

[0090] FIG. 12(d) shows a plot of specific capacity versus potential, with the discharge curves showing the change from S8 to Li2S n Two distinct plateaus are shown, corresponding to the reduction to (4≦n≦8) and then to Li2S2 / Li2S. These short-chain polysulfides are further converted to long-chain polysulfides and then to sulfur during the charging process.

[0091] By modifying the separator, polysulfides were bonded to the functional groups (-COOH, -OH, etc.) present on the MWCNT surface, reducing the shuttling of polysulfides and improving the specific capacity and stability.

[0092] Although the subject matter of the present invention has been described herein with reference to certain preferred embodiments thereof, other embodiments are possible. Therefore, the spirit and scope of the appended claims should not be limited to the description of the preferred embodiments contained therein. Moreover, precise and systematic details regarding all the above aspects are currently being worked out. The work of this invention is still in progress. It will be obvious to those skilled in the art to make various changes, modifications, and alterations to the invention described herein. It is intended that these various changes, modifications, and alterations are included in the present invention, provided they do not depart from the scope of the present invention. [Industrial Applicability]

[0093] (i) The present disclosure overcomes one or more shortcomings associated with conventional carbon-based hosts and their methods of manufacture in lithium-sulfur batteries.

[0094] The present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries.

[0095] The present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) to function as the cathode in lithium-sulfur batteries.

[0096] The present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) that exhibits high sulfur loading capacity in lithium-sulfur batteries.

[0097] The present disclosure provides washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) that is stable and provides long life for lithium-sulfur batteries.

[0098] The present disclosure provides a simple and economical method for the fabrication of washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries.

[0099] The present disclosure provides a lithium-sulfur cell comprising said washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) as a cathode.

Claims

1. A washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) with a surface area of ​​20 m for lithium-sulfur batteries was developed. 2 g -1 ~25m 2 g -1 and the pore size is 2 nm to 5 nm.

2. The washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) is 23 m 2 g -1 and a pore size of 2 nm to 5 nm.

3. A method for preparing washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) for lithium-sulfur batteries, comprising the steps of: i. Take carbon nanofiber powder (CNF) and dissolve it in HNO 3 to obtain carbon nanofiber (CNF) powder; ii. washing the carbon nanofiber (CNF) powder obtained in step (i) with deionized water and ethanol and drying to obtain functionalized carbon nanofiber foam (f-CNF); iii. Dispersing the functionalized carbon nanofiber foam in deionized water in a ratio ranging from 4:1 to 6:1 and sonicating to disperse; iv. adding glutaraldehyde, resorcinol, and sodium tetraborate decahydrate to the above obtained sonicated mixture of step (iii); v. Freezing and drying the mixture obtained in step (iv) to obtain 3D carbon nanofiber foam (CNF-f); vi. heat treating the 3D carbon nanofiber foam (CNF-f) to obtain a 3D carbonized carbon nanofiber foam (CCNF-f); vii. impregnating the 3D carbonized carbon nanofiber foam (CCNF-f) obtained in step (vi) with sulfur by heating the CCNF-f with elemental sulfur powder to obtain sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f); and viii. Washing the sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f) obtained in step (vii) with a solvent to remove excess sulfur to obtain washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW).

4. In step (i), the carbon nanofibers (CNFs) are treated with HNO at a temperature of 50° C. to 70° C. for 4 hours to 10 hours. 3 and the impregnation in step (vii) is carried out at a temperature of 160° C. to 250° C. for a period of 1 hour to 3 hours.

5. 4. The method of claim 3, wherein the functionalized carbon nanofiber foam (f-CNF) in step (iii) is dispersed in distilled water in a ratio of 5:

1.

6. 4. The method of claim 3, wherein in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature between 700°C and 900°C, more preferably, in step (vi), the 3D carbon nanofiber foam (CNF-f) is heat treated at a temperature of 800°C.

7. The method of claim 3, wherein the solvent is selected from any one or combination of toluene, chlorobenzene, toluene, p-xylene, and cyclohexane.

8. Lithium-sulfur cells, including: i. A cathode comprising washed sulfur-impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) [1]; ii. Anode [2]; iii. a separator [3]; and iv. Electrolytes [4].

9. The washed sulfur impregnated 3D carbonized carbon nanofiber foam (SCCNF-f-AW) had a concentration of 1.2 mg cm -2 ~1.8 mg cm -2 9. The lithium-sulfur cell of claim 8, exhibiting a sulfur loading in the range of

10. 9. The lithium-sulfur cell of claim 8, wherein the separator comprises a coating of functionalized multi-walled carbon nanotubes (f-MWCNTs) [5].